EXPRESSIVE SYNTAX AS A LINGUISTIC-STYLISTIC CATEGORY: HISTORY OF STUDY AND SYSTEM OF MEANS (International journal of artificial intelligence, 2026)
The article considers expressive syntax as a specific linguistic-stylistic category with its own conceptual and terminological apparatus and a developed system of expressive means. The history of the study of expressive syntax in Russian linguistics is traced — from the ideas of A.M. Peshkovsky and V.V. Vinogradov to modern concepts of O.V. Aleksandrova, E.M. Beregovskaya, M.Ya. Dymarsky. Based on the analysis of theoretical works, the main expressive syntactic constructions are systematised: parcelling, segmented constructions, inversion, various types of repetition and parallelism, ellipsis and aposiopesis, polysyndeton and asyndeton, rhetorical figures, gradation and antithesis. The text-forming potential of each of the identified means is characterised, and their systemic interconnection is shown. The article summarises the theoretical basis necessary for further study of expressive syntax in literary texts.